El área de logística en la Municipalidad Distrital de Maquia, periodo- 2019 - Montenegro Ahuanari, Cesar Augusto (2024)
We have a favorable opinion in our research on the logistics area of the District Municipality of Maquia, that is good, because this office is very important for the support and fluidity of all the requirements that enter the municipality, whether they are requirements of contractors or workers without contract or appointed by law 276, The rapid dispatch of service orders and purchase orders gives us an image of the good management of the logistics or supply area by all the professionals in this area, providing good service to workers, officials, suppliers and the population, who are satisfied with the District Municipality of Maquia. In the SPSS system we have 71% who think it is efficient, it is established that the logistics office is important in any state institution, because in this office all procurement procedures are developed for user care, only 06% think that this area is deficient, this negative opinion is because those who make the previous control in the logistics area, require compliance with OSCE standards, and those who do not have their files complete, are returned to regularize them in the shortest possible time. As a last opinion, I mention that the logistics or supply area of the District Municipality of Maquia, should have professionals appointed or hired for a fixed term, because this office is essential for the good image of this Municipality.